PENYULUHAN GIZI SEIMBANG DAN PENCEGAHAN TUBERKULOSIS, PENGUKURAN STATUS GIZI, PELATIHAN MEMBUAT CATATAN HARIAN MAKANAN DAN PEMBERIAN SUSU TERFORTIFIKASI PADA ANAK GIZI KURANG KONTAK DENGAN PENDERITA TUBERKULOSIS - Muttia Amalia; Hikmah Muktamiroh; Aulia Chairani (MADANI: Jurnal Pengabdian Kepada Masyarakat, 2018)
Province Jawa Barat statistic data reveals about 1.996 tuberculosis (TB) patient are living in Depok.Dinas Kesehatan Depok 2016 report that Depok has 3.942 undernutrition children. This condition could increase TB transmission and mortality caused by TB in children. The purpose of this activity were to inform and increase knowledge about balance nutrition and prevention of TB transmission by giving counseling and pocketbook, know how to do anthropometric assessment and make daily food journal, and distribute fortified milk to increase children nutrition. The target were healty parents and TB infected parents with children undernutrition. The results of this activities shows children with 2 children with severe underweight and severe wasting (8,7%) and 21 children with moderate underweight and moderate wasting (91,3%). The knowledge are measured by questionare. The result about balance nutrition shows that 12 persons with good result (2,2%), 5 persons with moderate result (21,7%) and 6 persons with poor result (26,1%). TB knowledge shows 20 persons with good results (87%) and 3 persons with poor result (13%). Training on making daily food journal were doing by simulation and practice. The responder return the result of daily food journal 3 weeks after the counseling done.